Ticagrelor and aspirin for the prevention of cardiovascular events after coronary artery bypass graft surgery. Issue 10 (18th February 2016) - Saw, Jacqueline; Wong, Graham C; Mayo, John; Bernstein, Victoria; Mancini, G B John; Ye, Jian; Skarsgard, Peter; Starovoytov, Andrew; Cairns, John
Abstract : Background: Ticagrelor was shown to reduce mortality in patients who underwent coronary artery bypass grafting (CABG), but its effect on graft patency is unknown. Methods: We performed a prospective, randomised, double-blind, placebo-controlled trial, comparing ticagrelor 90 mg twice daily versus placebo for 3 months added to aspirin 81 mg/day, following isolated CABG. Aspirin was started within 12 h, and study medication within 72 h after CABG. Primary outcome was graft occlusion on CT angiography (CTA) performed 3 months post CABG. Patients were followed to 12 months for death, myocardial infarction, stroke, repeat revascularisation and bleeding. Results: The study was terminated prematurely after randomising 70 patients between September 2011 and August 2014 because of slow recruitment. CTA was performed in 56 patients who completed >1 month of study drug. Graft occlusion occurred in 7/25 (28.0%) patients on ticagrelor and 17/31 (48.3%) on placebo, p=0.044. Of 207 analysable grafts, graft occlusion occurred in 9/87 (10.3%) with ticagrelor and 22/120 (18.3%) with placebo, p=0.112. Graft occlusion or stenosis ≥50% occurred in 10/87 (11.5%) ticagrelor vs 32/120 (26.7%) placebo, p=0.007. There was no major bleeding, but minor bleeding was higher with ticagrelor (31.4% vs 2.9%, p=0.003). In univariate analysis, ticagrelor use reduced graft occlusion (OR 0.32, 95% CI 0.10 to 0.97, p=0.047), which remained significant on multivariable analysis (OR 0.25, 95% CI 0.073 to 0.873, p=0.03). Conclusions: Ticagrelor added to aspirin after CABG reduced the proportion of patients with graft occlusion, and was a significant univariate and multivariable predictor of graft occlusion. These results are hypothesis-generating and should be confirmed in larger studies. Trial registration number: NCT01373411: Results.